Meningkatkan Kemampuan Bahasa Inggris: Pendekatan Kolaboratif antara Kuliah Kerja Nyata (KKN) dan Praktik Pengalaman Lapangan (PPL) di Anuban Jitjongrak School - Zulfa Della Affifah; Sri Lestari Handayani; Gufron Amirullah; Ari Widayanti; Mimin Ninawati; Nurafni Nurafni (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Real Work Lecture (KKN) collaborated with Field Experience Practices (PPL) in increasing student potential through English-based learning. English is a world language used to communicate between countries. The ability to speak English must be owned by everyone, especially elementary school children. English-based learning in education is often implemented with less attractive media, so students' interest in learning English is quite low. This article examines the implementation of work programs that meet the needs of Anuban Jitjongrak school community in improving English language skills. Language and facility limitations are a challenge for students in implementing appropriate work programs. The service method carried out KKN-PPL debriefing, observation and interviews, implementation of work programs, and evaluation of activities. As for the target in the implementation of this KKN-PPL are students at Anuban Jitjongrak School.